The preclinical efficacy, selectivity and pharmacologic profile of MK-5932, an insulin-sparing selective glucocorticoid receptor modulator - Brandish, P.; Anderson, K.; Baltus, G.; Bai, C.; Bungard, C.; Bunting, P.; Byford, A.; Chiu, C.; Cicmil, M.; Corcoran, H.; Euler, D.; Fisher, J.; et al. (2014)
Glucocorticoids are used widely in the treatment of inflammatory diseases, but use is accompanied by a significant burden of adverse effects. It has been hypothesized that gene- and cell-specific regulation of the glucocorticoid receptor by small molecule ligands could be translated into a therapeutic with an improved risk-benefit profile. MK-5932 is a highly selective glucocorticoid receptor modulator that is anti-inflammatory in vivo with an improved profile on glucose metabolism: Bungard et al. (2011). Bioorg. Med. Chem. 19, 7374-7386. Here we describe the full biological profile of MK-5932. Cytokine production following lipopolysaccharide (LPS) challenge was blocked by MK-5932 in both rat and human whole blood. Oral administration reduced inflammatory cytokine levels in the serum of rats challenged with LPS. MK-5932 was anti-inflammatory in a rat contact dermatitis model, but was differentiated from 6-methylprednisolone by a lack of elevation of fasting insulin or glucose levels after 7 days of dosing, even at high exposure levels. In fact, animals in the vehicle group were consistently hyperglycemic at the end of the study, and MK-5932 normalized glucose levels in a dose-dependent manner. MK-5932 was also anti-inflammatory in the rat collagen-induced arthritis and adjuvant-induced arthritis models. In healthy dogs, oral administration of MK-5932 exerted acute pharmacodynamic effects with potency comparable to prednisone, but with important differences on neutrophil counts, again suggestive of a dissociated profile. Important gaps in our understanding of mechanism of action remain, but MK-5932 will be a useful tool in dissecting the mechanisms of glucose dysregulation by therapeutic glucocortiocids. © 2013 Elsevier B.V.